Capacidade geral de combinação e análise multivariada de caracteres econômicos em couve-flor - Oliveira, Gustavo Evangelista (2015)
This study aimed to evaluate the population base for summer cauliflower breeding program and the best testers for this population in order to obtain hybrids. Also, it was aimed to study the correlation between yield and curd quality traits and the best selection methodology for these multiple traits. Cauliflower base population was obtained by crossing incompatible clones of “Piracicaba Precoce” (summer) with winter populations “Gigante Jaragua” and “Teresopolis Precoce”. Later on, summer x winter hybrids were intercrossed, obtaining a F2 bulk population, called PBVI. From PBVI population were selected 64 self-incompatible plants. The selected plants were propagated in vitro and the clones were crossed with one or more of seven testers, clones selected from cv. “Piracicaba Precoce”; “Santa Elisa” and “Vitória de Verão” populations. These hybrids constituted an incomplete diallel. The hybrids were evaluated for curd quality, yield and earliness traits. For each trait general combining ability (GCA) estimates were obtained. Canonical correlation between traits of quality and yield were obtained and Mulamba and Mock selection index, head quality index (HQI) and chart area index (CAI)were applied. There are variability in the population PBVI to curd quality, yield and earliness. “Piracicaba Precoce” and “Santa Elisa” testers have a better GCA in crossing with PBVI population, compared to other testers analyzed. The best hybrids were selected because present advantages over commercial standards. There is a high positive correlation between curd quality and yield traits. The HQI and IAG have higher selection gain.